2019
DOI: 10.1002/jclp.22731
|View full text |Cite
|
Sign up to set email alerts
|

Understanding grief reactions, thwarted belongingness, and suicide ideation in bereaved adolescents: Toward a unifying theory

Abstract: Objective: Childhood bereavement is linked to suicide-related behaviors in adolescence and adulthood, but candidate mechanisms through which bereavement may lead to suicide-related behaviors have not been explored. One candidate pathway is that grief reaction arising from bereavement lead to increased perceived burdensomeness and/or thwarted belongingness, resulting in increased suicide ideation. This cross-sectional study of bereaved adolescents explored indirect effects between grief reactions as distal pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 38 publications
0
30
0
Order By: Relevance
“…Despite extensive validation efforts, previous research has focused largely on adult populations. The INQ has been extended for use in multiple studies of children and adolescents (e.g., Buitron et al, 2016; Hill, Kaplow, Oosterhoff, & Layne, 2019; Opperman et al, 2015), including studies evaluating interventions designed to target perceived burdensomeness (e.g., Hill & Pettit, 2019) and to predict treatment outcomes among youth (Hains et al, 2019). However, scales initially developed for use with adults may not demonstrate equivalent performance when used with adolescents, which could be due to developmental differences in construct validity, reading skills, and/or the ability to interpret reverse‐scored questions (Benson & Hocevar, 1985; Locker et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive validation efforts, previous research has focused largely on adult populations. The INQ has been extended for use in multiple studies of children and adolescents (e.g., Buitron et al, 2016; Hill, Kaplow, Oosterhoff, & Layne, 2019; Opperman et al, 2015), including studies evaluating interventions designed to target perceived burdensomeness (e.g., Hill & Pettit, 2019) and to predict treatment outcomes among youth (Hains et al, 2019). However, scales initially developed for use with adults may not demonstrate equivalent performance when used with adolescents, which could be due to developmental differences in construct validity, reading skills, and/or the ability to interpret reverse‐scored questions (Benson & Hocevar, 1985; Locker et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although the correlation between the two is high, it is not high enough to be considered redundant ( r ≥ 0.90; Kline, 2015 ). This may be due to the inclusion in the PGS of items assessing alterations in personal identity which, due to its existential nature, is closely associated with suicidal ideation (Hill et al, 2019 ). On the other hand, from the interpersonal theory of suicide (Van Orden et al, 2010 ), it is proposed that the interaction between the belief of being a burden and that other people would benefit in some way from our death (perceived burden), as well as the feeling of loneliness, social isolation, and low social support (frustrated belonging), contributes very strongly to the presence of suicidal ideation.…”
Section: Discussionmentioning
confidence: 99%
“…Excerpts from psychological reactions (other than anxiety and depression) were all negative, and detailed an increase of various psychological problems. For example, Raphael et al (1990) identified increased neuroticism; Karakartal (2012) found increased levels of guilt and extreme fear; Stikkelbroek et al (2012) mention a prevalence of dysthymia and bipolar episodes as well as incidences of phobia and panic; Hill et al (2019) identifies reported higher levels of suicide ideation; and extreme cases found the need for psychiatric hospitalization (Harris, 1991).…”
Section: Reactions To the Deathmentioning
confidence: 99%